2007
DOI: 10.1186/1747-597x-2-4
|View full text |Cite
|
Sign up to set email alerts
|

Interferon alpha therapy for hepatitis C: treatment completion and response rates among patients with substance use disorders

Abstract: Background: Individuals with substance use disorders (SUDs) are at increased risk for hepatitis C viral infection (HCV), and few studies have explored their treatment responses empirically. The objective of this study was to assess interferon alpha therapy (IFN) completion and response rates among patients with HCV who had a history of comorbid SUDs. More data is needed to inform treatment strategies and guidelines for these patients. Using a medical record database, information was retrospectively collected o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Once we isolated germane articles, we collected relevant data and parameter values. While many literature reviews on treatment adherence exist, most limit their analysis to categorical reviews: the number of studies finding some correlation are reported but the papers do not include quantitative analysis of the reported correlation strength (Huckans, Loftis, Blackwell, Linke, & Hauser, 2007;Simoni et al, 2006;Bottonari et al, 2010). Our literature review is not on par with a meta-analysis of the literature.…”
Section: Data Compilationmentioning
confidence: 99%
“…Once we isolated germane articles, we collected relevant data and parameter values. While many literature reviews on treatment adherence exist, most limit their analysis to categorical reviews: the number of studies finding some correlation are reported but the papers do not include quantitative analysis of the reported correlation strength (Huckans, Loftis, Blackwell, Linke, & Hauser, 2007;Simoni et al, 2006;Bottonari et al, 2010). Our literature review is not on par with a meta-analysis of the literature.…”
Section: Data Compilationmentioning
confidence: 99%
“…In addition, those with factors associated with increased risk of rapidly progressive liver disease, such as HIV/HCV or HBV/HCV co-infection, are also candidates for treatment. A large retrospective Veterans Administration study has shown that individuals who are diagnosed with a substance use disorder (SUD) complete and respond to interferon-based HCV treatment regimens at similar rates to veterans without SUD's ( Huckans et al 2007 ). Because individuals, including injection drug users, with acute HCV infection may be highly responsive to interferon therapy, consideration should be given to early treatment during acute HCV infection ( Calleri et al 2007 ; Corey et al 2006 ).…”
Section: Viral Hepatitis Infections Liver Disease and Injection Drugmentioning
confidence: 99%
“…Recently, more prospective, controlled clinical trials of standard-of-care treatments for HCV infection in patients who are injection drug users have been performed. In 2007, seven treatment trials were published that included injection drug users ( Belfiori et al 2007 ; Calleria et al 2007 ; DeRosa, et al 2007 ; Grebely et al 2007 ; Huckans et al 2007 ; Krook et al 2007 ; Schaefer et al 2007 ) while other studies investigated factors related to the successful treatment of injection drug users including drug-drug interactions with methadone ( Berk et al 2007 ; Gupta et al 2007 ), immune responses of injection drug users ( Sergi et al 2007 ), and medication adherence ( Sylvestre and Clements, 2007 ). More studies are needed to enhance the development of effective treatment programs and clinical guidelines.…”
Section: Treatment Of Viral Hepatitis Infection In the Context Of Phamentioning
confidence: 99%
“…However, there is some evidence that treatment can be equally effective when patients have active psychiatric illness and drug use. 27-31 …”
Section: Introductionmentioning
confidence: 99%